Venture investment of marketing management of small trade enterprises: conditions and sources - K.M. Kraus (Marketing i Menedžment Innovacij, 2016)
The aim of the article. The main purpose of the article is to generalize the features and prospects and to substantiate the expediency of venture investment of marketing management of small trade enterprises in Ukraine and to identify effective forms of venture investment. The results of the analysis. The features of venture investment of marketing management of small trade enterprises of Ukraine are: distribution of risks between venture investor and small trade enterprise; flexibility of investment conditions; balance of risks and profits; orientation on increase in value of investments; participation in equity of investment object. Problems on the way of venture investment of the process of marketing management of Ukrainian small trade enterprises are: imperfect state tax regulation; imperfect state tax regulation; problems associated with the protection of the interests of owners and venture investors; underdeveloped infrastructure of venture investment; lack of interest of venture investors to invest small trade enterprises; lack of an effective system of interaction between venture investors and small trade enterprises; low levels of entrepreneurial culture in Ukraine. The key conditions of venture investment are: funds are provided without conditions returning via pre-specified period and without interest; funds are granted without collateral; venture investors are the owners of funds and investing in the enterprise, they become shareholders; the investor is actively involved in the discussion of financial, economic and technical questions on the rights of partner; investors investing in enterprises with a long payback period and high degree of uncertainty. The mechanism of venture investment of the process of marketing management of small trade enterprises should cover five key stages: development of venture investment strategy, search and selection of objects of venture investment, preparation and implementation of venture investment, management, monitoring and control of venture investment. There two groups of investors in the system of venture investment: corporate and individual investors. Significant role in the financing of small trade enterprises can have «business angels» who invest their own funds, while venture capital firms operating resources of institutional investors. «Business angels» can be divided into: individual investors with significant personal funds and invest them in business of relatives and friends; group of people who are entrepreneurs in a certain or related sectors. The advantages of attracting «business angels» to invest in the process of marketing management of small trade enterprises in Ukraine include: simplicity in documentation and flexible decision-making; the possibility of obtaining financial resources despite the high risk business enterprise; small expensive-attracting of «business angels» due to their low rate of return; opportunity to receive not only financial support but also valuable experience and knowledge of «business angels» to the successful development of enterprise; territorial accessibility of «business angels». Conclusions and directions of further researches. Venture investors that invest their own funds in small trade enterprises can not only get profit in the future. Symbiosis of venture investor and entrepreneur often provides synergy effect from combining their special knowledge, business contacts and managerial experience.